Crude palm oil (CPO) extraction using hot compressed water (HCW) - Md. Sarip, Mohd. Sharizan (Elsevier B. V., 2016)
Hot compressed water extraction (HCWE) is a promising alternative technology which has proven to be successful in many applications. In this study, hot compressed water extraction (HCWE) was applied in the extraction of crude palm oil (CPO) from palm mesocarp. The operating conditions investigated were pressure of 30, 40 and 50 bar with varied temperature ranging from 120 to 180 degrees C through semi-batch extraction of 10 min interval and total extraction time of 60 min. The CPO yield, free fatty acids (FFA) content through HCWE process was analysed. Scanning electron microscopy (SEM) study on various palm mesocarp fibres undergone HCWE process at various conditions was also performed. The extracts formed three distinguished layers; oil, oil-water emulsion and water. The maximum CPO extracted in the oil layer was 0.541 +/- 0.005 (g-oil/g-dried mesocarp) with averaged FFA of 0.81 +/- 0.08% at the optimum operating condition of 160 degrees C and 50 bar. CPO recovered from the emulsion was 0.159 +/- 0.004 g-oil/g-dried mesocarp giving a total CPO extracted at 0.700 +/- 0.005 g-oil/g-dried mesocarp. SEM micrographs were used to assist understanding of the mechanism that took place during the experimental conditions of HCWE. The time dependence of the compounds was well represented by the second order mass transfer model. The mechanism of CPO extraction from palm mesocarp using HCWE was also explained through this study.